(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article deals with the distinctive with their ancient history, unique customs and traditions, language and culture that constantly attract the attention of the world community thanks to the depth of content, vivid images, national spirit and philosophy.